A Head-Mounted Spectacle Frame for the Study of Mouse Lens-Induced Myopia - Yangshun Gu; Baisheng Xu; Chunfei Feng; Yang Ni; Qin Wu; Chixin Du; Nan Hong; Peng Li; Zhihua Ding; Bo Jiang (Journal of Ophthalmology, 2016)
The mouse model has been widely employed to explore the mysteries of myopia. For now, existing techniques for induction of experimental myopia in mice can be classified into three types: (1) devices directly glued to the fur; (2) devices attached using a combination of glue and sutures; (3) devices attached using a skull-mounted apparatus. These techniques each have its advantages, disadvantages when considering the devices stability, safety, complexity, effectiveness, and so forth. Thus, techniques for myopia induction in mice have yet to be further refined to popularize the applications. In this pilot study, we introduce a new head fixation device named the head-mounted spectacle frame apparatus for the study of mouse lens-induced myopia. Surgical procedures for device attachment were relatively simple and easy to learn in our study. Effective myopia induction was validated by retinoscopy refraction and axial length measurement using optical coherence tomography. In addition, it showed improved compliance and reliable safety when compared to the published methods. The head-mounted spectacle frame apparatus provides a new choice for the study of lens-induced myopia in mouse. It also allows for the use of form deprivation, making it attractive for future experimental mouse myopia trials.